Inside Agile Family: Software Development Methodologies - Kumar, Rakesh; Maheshwary, Priti; Malche, Timothy (International Journal of Computer Sciences and Engineering, 2019)
Software requirements are adapting by the customer to adjust in new environment because business environment is very dynamic in current era. Struggling for appropriate agile processes for development environments of Software developers and project managers is going on till the appropriate process is not matched. Need to adapt in a complex business environment is being faced by organization for helping them in continuous change and transformation. Organization agility is being gaining strategic advantages and market success in these conditions, for maintaining and achieving requirement of agility are agile techniques, architectures, tools, methods and able to react to change requirements in real time. In this research paper various agile family methodologies like AM, XP, Scrum Development, Feature FDD, DSDM, ASD, Kanban, LSD, Scrumban, RAD, Crystal, AUP, DAD has been studied and compared on the basis of various parameters along with their relationship. The research will help future developers to get new ideas about the methods for development along with selection of the right methodology for the product development.